Equation and Adequation: The World Traced by the Phillips Curve. Issue 1 (7th March 2017) - Mann, Geoff
Abstract: This paper considers the power of abstract formalization in capitalism, via an account of the politics and geography of an equation. The equation in question lies behind the Phillips curve, which describes the relation between price inflation and unemployment or output. I examine the evolution of the equation and its relation to macroeconomics' renewed emphasis, since the late 1960s, on long‐run monetary neutrality. Considering the Phillips curve and its theoretical and technical armature as social practice, I discuss some of the political and distributional questions that arise from the mode of spatial and temporal abstraction particular to modern macroeconomic analysis and policy‐making. The paper has three parts: a brief history of the Phillips curve, an examination of its modern equation‐form, and an analysis of its part in the dialectical process of "real abstraction", through which logical space and time prioritize and produce both the spatial "macro" and the temporal "long‐run".